Cellular and molecular mechanisms involved in the neuroprotective effects of VEGF on motoneurons - Lladó, Jerònia; Tolosa, Laia; Olmos, Gabriel (Frontiers in Cellular Neuroscience, 2013)
Vascular endothelial growth factor (VEGF), originally described as a factor with a regulatory role in vascular growth and development, it is also known for its direct effects on neuronal cells. The discovery in the past decade that transgenic mice expressing reduced levels of VEGF developed late-onset motoneuron pathology, reminiscent of amyotrophic lateral sclerosis (ALS), opened a new field of research on this disease. VEGF has been shown to protect motoneurons from excitotoxic death, which is a relevant mechanism involved in motoneuron degeneration in ALS. Thus, VEGF delays motoneuron degeneration and increases survival in animal models of ALS. VEGF exerts its anti-excitotoxic effects on motoneurons through molecular mechanisms involving the VEGF receptor-2 resulting in the activation of the PI3-K/Akt signaling pathway, upregulation of GluR2 subunit of AMPA receptors, inhibition of p38MAPK and induction of the anti-apoptotic molecule Bcl-2. In addition, VEGF acts on astrocytes to reduce astroglial activation and to induce the release of growth factors. The potential use of VEGF as a therapeutic tool in ALS is counteracted by its vascular effects and by its short effective time frame. More studies are needed to assess the optimal isoform, route of administration and time frame for using VEGF in the treatment of ALS.